Height and weight gain after total correction of Fallot's tetralogy. Issue 4 (April 1978) - Page, R E; Deverall, P B; Watson, D A; Scott, O
Abstract : In a consecutive series of 100 cases of Fallot's tetralogy undergoing total correction, the mean birthweight was found to be just below the 50th centile. Blalock-Taussig or Waterston shunts were performed in 45 patients. Before their shunt operations a significant number of patients had become retarded in height and weight development but after the shunt operations many patients showed accelerated height and weight gain. Of the 73 patients followed up 2 years after correction, 23 had experienced accelerated development in both weight and height, but 11 patients remained on or below the 3rd centile for weight and height. In terms of the age at shunting, the oxygen saturation immediately before total correction, the age at total correction, the number of ventriculotomy patch repairs, and the post-correction ventricular pressure ratios, no significant difference could be detected between those 23 patients who had undergone accelerated development and those 11 who had remained retarded. More shunts, particularly of the Waterston type, were performed in the retarded group.